TUTURAN IMPERATIF DAN IMPLIKATUR PERMINTAAN DALAM BAHASA JEPANG (Kajian Pragmatik) - Dewi Saparina Halibanon; Alya Hasna (Jurnal Sastra - Studi Ilmiah Sastra, 2021)
This essay is entitled "Imperative Speech and Implicature of Demand in Japanese". This imperative discourse and the implicature of appeal analysed through a pragmatic approach. The purpose of this study is to describe a self-assertive form of speech and the demand implicature of the Japanese language in the anime Natsume Yuujinchou as the object of research. The author uses a qualitative method with a transformational approach. From this study, the author found a variety of request imperative utterances, namely demand assertive and intransitive imperative. Besides, there are also various utterances of request for masu form, subject matter for an adjective, prohibition, wish, invitation, becoming, and command.